2012
DOI: 10.1161/atvbaha.111.237271
|View full text |Cite
|
Sign up to set email alerts
|

Short Telomere Length, Myocardial Infarction, Ischemic Heart Disease, and Early Death

Abstract: Objective-We tested the hypothesis that short telomere length is associated with increased risk of myocardial infarction, ischemic heart disease, and early death. Methods and Results-We measured leukocyte telomere length in 2 prospective studies of 19 838 Danish general population participants from the Copenhagen City Heart Study and the Copenhagen General Population Study. Participants were followed for up to 19 years for incident myocardial infarction (nϭ929), ischemic heart disease (nϭ2038), and death (nϭ43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
133
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 34 publications
7
133
1
2
Order By: Relevance
“…The cohort represents the full range of socioeconomic status (SES) in the general population of New Zealand' s South Island and is primarily white. Assessments were carried out at birth and at ages 3,5,7,9,11,13,15,18,21,26,32, and, most recently, 38 years, when 95.4% of the 1007 living study members underwent assessment in 2010 to 2012. At each assessment wave, each study member is brought to the Dunedin Research Unit for a full day of interviews and examinations.…”
Section: Participantsmentioning
confidence: 99%
“…The cohort represents the full range of socioeconomic status (SES) in the general population of New Zealand' s South Island and is primarily white. Assessments were carried out at birth and at ages 3,5,7,9,11,13,15,18,21,26,32, and, most recently, 38 years, when 95.4% of the 1007 living study members underwent assessment in 2010 to 2012. At each assessment wave, each study member is brought to the Dunedin Research Unit for a full day of interviews and examinations.…”
Section: Participantsmentioning
confidence: 99%
“…Regarding cause-specific mortality such as cardiovascular disease (CVD) mortality and cancer mortality, results have also been inconsistent. The associations reported between LTL and CVD indicate a modest inverse link (7)(8)(9)(10), but are heterogeneous with regards to CVD mortality (11)(12)(13). The associations of LTL with cancer seem to be even more complex.…”
mentioning
confidence: 99%
“…Mutations that decrease telomerase and cause short telomeres in humans lead to a spectrum of premature-onset diseases and conditions collectively termed "telomere syndromes," which share many features of the common diseases of aging in the human population (Armanios and Blackburn 2012). Multiple independent studies have found impaired human telomeric DNA length maintenance to be associated with a wide range of diseases and for several age-related diseases to predict future risks and outcomes including mortality (Von Zglinicki et al 2000;Samani et al 2001;Cawthon et al 2003;Panossian et al 2003;Valdes et al 2005;Bischoff et al 2006;Harris et al 2006;MartinRuiz et al 2006;Bakaysa et al 2007;Brouilette et al 2007;Fitzpatrick et al 2007Fitzpatrick et al , 2011Aubert and Lansdorp 2008;Farzaneh-Far et al 2008;Kimura et al 2008;Epel et al 2009;Njajou et al 2009;Astrup et al 2010;Codd et al 2010Codd et al , 2013Salpea et al 2010;Willeit et al 2010a,b;Zee et al 2010;Strandberg et al 2011;Wentzensen et al 2011;Yaffe et al 2011;Honig et al 2012;Lee et al 2012;Weischer et al 2012;Bojesen 2013;Muezzinler et al 2013;Gardner et al 2014;Haycock et al 2014;Walsh et al 2014).…”
mentioning
confidence: 99%
“…A recent study incorporating data from the National Health and Nutrition Examination Survey (NHANES) 1999-2002, a large, nationally representative, ethnically and socioeconomically diverse sample, reported that sex, race-ethnicity, and socioeconomic status (SES) moderated the associations between TL and mortality in older individuals (Needham et al 2012). However, while some human cohort studies have found shorter PBMC TL or LTL is associated with increased mortality (Cawthon et al 2003;Martin-Ruiz et al 2006;Bakaysa et al 2007;Farzaneh-Far et al 2008;Kimura et al 2008;Epel et al 2009;Astrup et al 2010;Willeit et al 2010b;Fitzpatrick et al 2011;Honig et al 2012;Lee et al 2012;Weischer et al 2012), others have not (Bischoff et al 2006;Harris et al 2006;Njajou et al 2009;Strandberg et al 2011). These inconsistencies in the literature may be due to differences in study cohorts, sample sizes, assay methods, and other methodological differences (Bojesen 2013).…”
mentioning
confidence: 99%